Malaxis malipoensis (Malaxideae: Orchidaceae), a new species from Yunnan, China - Meng, Yufang; Hu, Aiqun; Yi, Qifei; Xing, Fuwu (Phytotaxa, 2014)
Malaxis Solander ex Swartz (1788), the main genus of the tribe Malaxideae (Orchidaceae), consists of about 300 species that are widespread in the tropics and subtropics of the old and new worlds. Only one species of this genus, namely Malaxis monophyllos (Linneaus, 1753: 947) Swartz (1800: 234), has previously been recorded from China (Chen et al. 2009). The taxonomy of the genus is still obscure, even though many researchers have attempted clarification in the past 200 years. (Ridley 1888, Smith 1930, Schlechter 1911, Seidenfaden 1978, Dressler 1993). Undoubtedly, Malaxis is polyphyletic (Cameron 2005, Pridgeon et al. 2006). Most authors have followed treatments of Schlechter (1911) and Seidenfaden (1978) in accepting a broadly defined Malaxis (Smith 1930, Dressler 1993, Chen, 1999).